Importance of thrombosis and thrombolysis in silent ischaemia: comparison of patients with acute myocardial infarction and unstable angina. Issue 2 (February 1994) - Gurfinkel, E.; Altman, R.; Scazziota, A.; Rouvier, J.; Mautner, B.
Abstract : OBJECTIVE--To investigate whether plaque rupture and thrombosis have a role in silent ischaemia as well as in unstable angina. DESIGN--Prospective analysis of the results of haemostatic diagnostic tests at the moment of developing silent ischaemia at rest. SETTING--Coronary care unit. PATIENTS--22 patients with acute myocardial infarction, 12 patients with symptomatic angina (unstable angina), and 10 normal volunteers (control group). INTERVENTIONS--Continuous cardiac monitoring detected 15 asymptomatic episodes (silent ischaemia) in 6 patients with unstable angina. Blood samples were obtained at admission and when an asymptomatic alteration was detected and 10 minutes later. MAIN OUTCOME MEASURES--Comparisons of concentrations of tissue plasminogen activator, urokinase type plasminogen activator, tissue plasminogen activator inhibitor-1, cross-linked fibrin degradation products, von Willebrand factor, and thrombin-antithrombin III complexes in patients and controls at admission; same comparisons in patients with silent ischaemia at the start of an episode and 10 minutes later. RESULTS--Tissue plasminogen activator concentrations were raised at admission in patients with acute myocardial infarction (mean (SD) 14.2 (6) ng/ml) and in patients with unstable angina (10.1 (2.5) ng/ml) in comparison with controls (5.1 (2.7) ng/ml, p < 0.01 and < 0.05 respectively). There was no differences between the two groups of patients, however. Similar results were observed at the start of a silent ischaemic episode (9.8 (1.9) ng/ml) and 10 minutes later (10.5 (2.9) ng/ml) compared with controls (p < 0.05). Tissue plasminogen activator inhibitor-1 concentrations were raised in patients with acute myocardial infarction (45.1 (15) ng/ml) compared with volunteers (20.6 (16) ng/ml, p < 0.01). In patients with silent ischaemia tissue plasminogen activator inhibitor-1 concentrations were slightly but not significantly increased. Concentrations of cross-linked fibrin degradation products (D dimer) increased during unstable angina (2150 (350) ng/ml) and silent ischaemia (2270 (450) ng/ml) compared with the concentrations in volunteers (340 (80) ng/ml) and patients with acute myocardial infarction (310 (120) ng/ml; p < 0.01). CONCLUSIONS--The results suggest that thrombosis mediates the pathophysiological mechanisms of silent ischaemia and unstable angina.